2014
DOI: 10.1002/art.38799
|View full text |Cite
|
Sign up to set email alerts
|

Dkk‐1–Mediated Inhibition of Wnt Signaling in Bone Ameliorates Osteoarthritis in Mice

Abstract: Objective. Wnt signaling is a master regulator of joint homeostasis, but its role in osteoarthritis (OA) remains unclear. This study was undertaken to characterize the activation of Wnt/␤-catenin in knee joints of mice with OA and to assess how inhibiting this pathway in bone could affect cartilage.Methods. OA was induced by partial meniscectomy in Topgal mice and in transgenic mice overexpressing Dkk-1 under the control of the 2.3-kb Col1a1 promoter (Col1a1-Dkk-1-Tg mice). Wnt/␤-catenin activation was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 52 publications
(71 reference statements)
1
97
0
Order By: Relevance
“…Furthermore, DKK1 is a canonical upstream inhibitor of Wnt signaling [33,34]; this study showed that LiCl can counteract the DKK1 inhibition of Wnt signaling. These findings indicate that LiCl regulated BMSC differentiation in a Wnt signaling-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DKK1 is a canonical upstream inhibitor of Wnt signaling [33,34]; this study showed that LiCl can counteract the DKK1 inhibition of Wnt signaling. These findings indicate that LiCl regulated BMSC differentiation in a Wnt signaling-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Altered activity of Wnt signaling in chondrocytes may involve osteoclastic activity in subchondral bone growth plates leading to sclerosis or osteophyte formation at the edges of joints (165,166). In addition, Dickkopf-1 (Dkk1) is an inhibitor of this pathway, and its overexpression in bone leads to thicker and stiffer bones, retarding cartilage degradation (167). Moreover, the deletion of sclerostin, another Wnt antagonist, increased the severity of OA, although no changes in cartilage were observed (168).…”
Section: Cartilage Interface With Subchondral Bone In Oamentioning
confidence: 97%
“…Indeed, chondrocyte-specific deletion of MMP13 alleviated OA in mice; the Wnt family members were candidates for the regulation of MMP13 expression in chondrocytes because its expression was increased in chondrocytes from mice with conditional activation of β-catenin (12). Cumulative data showed that Wnt activity is low under physiological conditions, and activation of Wnt signaling contributes to cartilage breakdown in OA (13,14). The modulation of Wnt inhibitors had significant effects on chondrocyte catabolism of mice.…”
mentioning
confidence: 99%
“…The modulation of Wnt inhibitors had significant effects on chondrocyte catabolism of mice. Indeed, loss of sclerostin enhanced cartilage degradation (15) and the overexpression of Dkk-1 alleviated OA (14). Despite the hypoxic status of cartilage (16), the involvement of hypoxia in regulating Wnt signaling and MMP13 expression in cartilage is still unclear.…”
mentioning
confidence: 99%